An anatomical study of arcuate foramen and its clinical implications: a case report. Issue 1 (December 2016) - Afsharpour, Salman; Hoiriis, Kathryn; Fox, R.; Demons, Samuel
Abstract Background The objective of this paper is to describe the relationship of the vertebral artery (VA) to the Atlas (C1) in the sub-occipital region in the presence of arcuate foramen; and discuss the clinical implications related to manual therapies and surgical implications related to screw placement. This study is an anatomical cadaveric case report of symmetrical bilateral lateral and dorsal arcuate foramina on the C1 dorsal arch. Case Presentation Out of 40 cadavers that were available for use in teaching anatomy in the university setting, three presented with anomalies of the C1 dorsal arch. The sub-occipital regions were skillfully prosected to preserve related structures, especially VAs, sub-occipital and greater occipital nerves. Visual observations, photographs, measurements, and radiographic examinations were performed between January 15, 2014 and August 25, 2014. One cadaver (Specimen A) presented with complete bilateral ossified arcuate foramina, and two presented with partial ossification of the atlanto-occipital membrane. Specimen A presented the bilateral anomaly which is almost symmetrical. The VAs were found passing through double foramina (lateral and dorsal) on each side. Conclusions Arcuate foramina have been shown to be commonly found anomalies with highly variable shapes and sizes, even in the same individual with a bilateral condition. This study found a rare type of the anomaly associated with the C1 dorsal arch, which protected the VA against manual pressure. However, VA, in this case, would be more susceptible to dissection. The presence of the arcuate foramen would also complicate screw placement during surgery. Clinical pre-screening for signs of vertebrobasilar insufficiency is important for chiropractic and manual therapies.